Analisis Budaya Kerja Disiplin Pegawai Negeri Sipil: Studi pada beberapa Pemerintah Daerah di Sumatera Barat - Frinaldi, Aldri (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2011)
Improving the work culture of discipline was in line with the increase of the implementation of local governance. This issue of discipline work culture in the reform era was highlighted by many experts, including the working culture of civil servants in the City District and Provincial Governments. This research is based on the philosophy of phenomenology. Qualitative approach supported by quantitative was used in this study. The result of this study indicated that unlicensed improving the discipline of civil servants is very urgently needed because the average propensity of discipline work culture of civil servants in local government in West Sumatra is still low. Changes in work culture of discipline can be done by placing civil servants in accordance with their skills and expertise adapted to the volume of workload, so there is no hoarding of the number of civil servants in a unit while the other units experiencing a shortage of civil servants.Kata Kunci: Budaya kerja, disiplin kerja, Pegawai Negeri Sipil